2017
DOI: 10.3390/su9071268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Half-Precast Concrete Slab System on Construction Productivity

Abstract: A half-precast concrete slab system (HPCSS) is reported to exhibit excellent structural performance when compared with traditional slab systems. However, there is a lack of extant research examining the construction issues of an HPCSS. Thus, in this study, we analyze the construction process and productivity of applying an HPCSS by using a simulation method with the data collected from an actual construction case. The results indicate that (i) the construction productivity of HPCSS is 1.7 times that of a tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
(31 reference statements)
0
9
0
2
Order By: Relevance
“…Instead, the quality assurance can be improved by prefabrication in factory. Moreover, it is more environmental friendly and the productivity is higher to adopt prefabricated reinforced concrete elements compared to traditional cast-insitu method [16,31,14].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the quality assurance can be improved by prefabrication in factory. Moreover, it is more environmental friendly and the productivity is higher to adopt prefabricated reinforced concrete elements compared to traditional cast-insitu method [16,31,14].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the application of this method needs less crew to finish the slab construction. Besides, as half-slab is only used as formwork, the design strength of the slab is focused on receiving both self-weight of concrete and its live load during installation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, semi-precast slab systems have been adopted to reduce the weight, and in situ concrete overtopping is practised in many projects (Pessiki et al, 1995). Cho et al (2017) investigated the construction productivity of semi-precast slab systems and reported that it is 1.7 times that of a conventional in situ RC slab system. Despite of widely recognised practice, the knowledge on the material and structural performance of semi-precast-RC slab system is limited.…”
Section: Introductionmentioning
confidence: 99%